Developing an Interactive Digital Comic Integrated with Multimedia Visualization for Lithosphere Learning in Geography Education - Sumardi, Muh Ammar; Maliki, Rendra Zainal; Khairurraziq, Khairurraziq; Supriyatman, Supriyatman (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
The integration of digital technology into geography education requires innovative learning media capable of facilitating students’ understanding of abstract concepts. One topic that often presents learning challenges is the lithosphere, as geological processes such as tectonism, volcanism, and seismic activity are difficult to visualize through conventional instructional resources. This study aimed to develop an interactive digital comic as a learning medium for lithosphere material in Grade X senior high schools and to evaluate its feasibility for classroom use. The study employed a Research and Development (R&D) approach using the ADDIE model, limited to the Analysis, Design, and Development stages. The research was conducted in four schools in Palu, Indonesia, involving one material expert, one media expert, four geography teachers, and 65 students. Data were collected through observations and questionnaires and analyzed using descriptive quantitative techniques. The developed product integrated comic-based storytelling, interactive three-dimensional visualizations created with Assemblr Edu, web-based accessibility through Canva, and digital assessment activities. The validation results indicated that the interactive digital comic achieved a feasibility score of 96.66% from the material expert and 86.66% from the media expert. Practitioner validation scores ranged from 84% to 98%, while student responses reached an overall score of 89.96%. These findings demonstrate that the developed media is highly feasible for geography learning. The study highlights the potential of integrating visual storytelling, interactive multimedia, and digital technologies to support technology-enhanced geography education and facilitate students’ engagement with complex lithosphere concepts.